Rancangan Modul Cognitive Behavioral Art Therapy (CBAT) untuk Menurunkan Gejala Trauma Pada Korban Kekerasan Dalam Pacaran: Penelitian - Nurbillah, Sheila Aisma Nurbillah; Dewi Sartika; Lilim Halimah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Dating violence can lead to mental health disorders such as Posttraumatic Stress Disorder (PTSD). PTSD sufferers due to this violence generally experience cognitive distortions such as catastrophizing, overgeneralization, fortune telling, and personalization. PTSD not only has psychological impacts but also affects the brain and body. Therefore, interventions that integrate CBT and Art Therapy concepts are needed to stimulate and externalize emotions. Currently, there is no integrative module specifically designed to treat PTSD. This study aims to develop a Cognitive Behavioral Art Therapy (CBAT) module to reduce trauma symptoms in victims of dating violence. This module was developed based on Marcia Rosal's CBAT theory. Content validity was tested by three psychologists with expertise in CBT and art therapy, showing an Aiken's score of 1 (high). The trial was conducted on three early adult women (18–25 years old) victims of dating violence who experienced PTSD. The results of the Wilcoxon Signed Rank test showed a difference in PTSD scores before and after the intervention. This module consists of eight sessions with a duration of 50–90 minutes per session.